Feasibility study of structured diagnosis methods for functional dyspepsia in Korean medicine clinics - Jeong Hwan Park; Soyoung Kim; Jae-Woo Park; Seok-Jae Ko; Sanghun Lee (Integrative Medicine Research)
Background: Functional dyspepsia (FD) is the seventh most common disease encountered in Korean medicine (KM) clinics. Despite the large number of FD patients visiting KM clinics, the accumulated medical records have no utility in evidence development, due to being unstructured. This study aimed to construct a standard operating procedure (SOP) with appropriate structured diagnostic methods for FD, and assess the feasibility for use in KM clinics. Methods: Two rounds of professional surveys were conducted by 10 Korean internal medicine professors to select the representative diagnostic methods. A feasibility study was conducted to evaluate compliance and time required for using the structured diagnostic methods by three specialists in two hospitals. Results: As per the results of the professional survey, five questionnaires and one basic diagnostic method were selected. An SOP was constructed based on the survey results, and a feasibility study showed that the SOP compliance score (out of 5) was 3.45 among the subjects, and 3.25 among the practitioners. The SOP was acceptable and was not deemed difficult to execute. The total execution time was 136.5 minutes, out of which the gastric emptying test time was 129 minutes. Conclusion: This feasibility study of the SOP with structured diagnostic methods for FD confirmed it was adequate for use in KM clinics. It is expected that these study findings will be helpful to clinicians who wish to conduct observational studies as well as to generate quantitative medical records to facilitate Big Data research. Keywords: Big Data, Dyspepsia, Korean medicine, Feasibility studies, Observational study